Psychometric Reevaluation of Parental Press for Academic Achievement and Postsecondary Planning Scale. (September 2016) - Bates, Samantha; Ball, Annahita; Wilks, Scott
Objective: Psychometric details of the Parental Press for Academic Achievement and Postsecondary Planning Scale (PPS), developed by Chicago Consortium of Chicago School Research, are scarce. The purpose of this study was to reexamine the properties of this 7-item measure. Method: The study utilized cross-sectional, self-reported data from 100 low-income, first-generation undergraduate students at a university in the southern United States. Results: Factor analysis on the PPS revealed two dimensions with all items loaded, accounting for 81.44% of the variance. Reliability of the PPS was sound, that is, average interitem correlation was .62 and Cronbach's α and split-half coefficients were .918 and .923, respectively. Convergent validity was suggested via significant correlations between the PPS and its theoretically similar constructs, that is, valuation of high school ( r = .32) and parental support for college ( r = .82). Conclusion: The PPS appears to be psychometrically appropriate for appraising students' perceptions of parental support for academic success and postsecondary education.